Subcritical Water Extraction of Rosmarinic Acid from Lemon Balm (Melissa officinalis L.) and Its Effect on Plant Cell Wall Constituents - Ana Atanasova; Ani Petrova; Desislava Teneva; Manol Ognyanov; Yordan Georgiev; Nenko Nenov; Petko Denev (MDPI AG, 2023)
Rosmarinic acid (RA), an ester of caffeic acid and 3,4-dihydroxyphenyllactic acid, is a potent radical scavenger, a chelator of prooxidant ions, and an inhibitor of lipid peroxidation. RA-containing extracts are widely used natural antioxidants in food products, and many herbal preparations and food supplements, containing RA, are marketed with claims of beneficial health effects. The current study investigated the effectiveness of subcritical water extraction (SWE) for the recovery of RA from lemon balm (Melissa officinalis), as a "green" alternative to conventional hydro-alcoholic extraction. Different durations (10 min and 20 min) and extraction temperatures (100 °C and 150 °C) were applied. Subcritical water applied at a temperature of 100 °C was equally efficient as 50% ethanol in extracting RA. However, the further elevation of temperature to 150 °C decreased RA content by up to 20% due to thermal degradation. The content of RA in dried extracts was between 2.36% and 5.55% and the higher temperature of SWE increased extract yield by up to 41%. The higher extraction yield resulted from the degradation of plant material by subcritical water as evidenced by the increased extraction and degradation of proteins, pectin, and cellulose. These results reveal that SWE is an efficient technology for the extraction of RA and other antioxidants from lemon balm at reduced extraction time and without the use of toxic organic solvents. Furthermore, by modification of SWE conditions, dry extracts with different purity and content of RA are obtained. These extracts could be used in the food industry as food antioxidants, or in the development of food supplements and functional foods.